Egyptian faience glazing by the cementation method part 1: an investigation of the glazing powder composition and glazing mechanism - Matin, M; Matin, M (Elsevier, 2011)
In cementation glazing, for various reasons, there are significant differences between the composition of the glass phases present in the faience microstructure and the glazing powder composition. Furthermore, in this glazing method, the glazing powder should perform more functions, which are: producing a shiny and smooth glaze coating, producing a firm capsule surrounding objects entirely (to prevent adhesion between sintered glazing mixture and the melting glaze coating), and, finally, producing a porous and friable sintered glazing mixture for safe and easy removal of buried objects. It is obvious that these functions also have significant effects on the glazing powder composition and constitution. Therefore, analytical data on faience glass phases are very unlikely to reflect the strict composition and constitution of the original glazing powder properly. Accordingly, the composition and constitution of cementation glazing powder have remained obscure for a long time. These data are particularly crucial factors for cementation replication experiments and, consequently, for our awareness of the ancient faience production. In this paper, a series of cementation replication experiments have been conducted in an attempt to provide further clarification of these issues. In addition, as a comparative indicator for alkali and copper vaporisation, a small piece of rock quartz was placed separately above the glazing powder. After firing, the appearance of the faience objects and quartz pieces and the microstructures and chemical compositions of a select group of samples, obtained using Scanning Electron Microscopy – Energy Dispersive Spectroscopy (SEM-EDS), were investigated. The discussion has focused mainly on issues such as the raw materials and their contribution in the glazing process, the criteria for determining the faience glazing methods, the necessary quantity of alkalis for a successful cementation glazing, and, particularly, the glazing mechanism.